(untitled) (International Journal of Medical and Surgical Sciences, 2014)
Research oriented to bone regeneration and reconstruction has been growing and national and international research teams have complied with the development of sustained and sustainable research criteria. The aim of this work is to present the results of investigations realized by different centers to which the author is affiliated, making an analysis of maxillary sinus reconstruction for dental implants. We revised research during the last 6 years related to the surgical technique, anatomical analyses, and definition, as well as choice of bone graft. We determined the main conclusions of the analyses, innovative research to optimize efficiency in major sinus reconstruction was established, as was the technique modification for different cases.